Adoption Barriers and Drivers of Accounting Information Systems in Developed and Developing Nations: A Systematic Review - Anggi Ayuni Dewi; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the drivers and barriers influencing the adoption of Accounting Information Systems (AIS) in developed and developing countries using a Systematic Literature Review (SLR). Fifteen articles published from 2021 to 2025 were reviewed, sourced from Scopus, Emerald Insight, ScienceDirect, Google Scholar and SINTA. The review followed PRISMA procedures and applied inclusion and exclusion criteria to ensure relevance and methodological rigor. The findings reveal four major determinants of AIS adoption, technological, organizational, individual and environmental factors. Developing countries face structural barriers such as limited digital literacy, financial constraints, inadequate infrastructure and weak regulatory support. In contrast, developed countries encounter more advanced challenges, including system complexity, high integration costs and heightened concerns regarding data security and privacy. These distinctions demonstrate a persistent digital divide across nations. This study contributes by mapping AIS adoption factors through TAM, TOE and UTAUT frameworks and providing practical insights for context-specific AIS implementation strategies.